Penerapan Barthel Index Terhadap Tingkat Kemandirian Aktivitas Harian Lansia Jamaah Lansia Masjid KH. Ahmad Dahlan Banjarmasin - Alit Suwandewi; Muhammad Ferdy Baihaqi; Mimin Hafizatul Maulida; Maryam Maryam; Sonia Sonia (Pusat Riset dan Inovasi Nasional, 2024)
Elderly is a process of human growth and development does not occur suddenly, namely developing from infants to become elderly. Everyone's physique and behavior changes when they reach a certain age is normal. Elderly is the end of the aging process that has reached the age of 60 and over. As we get older, organ function decreases with age, which has an impact on the ability of the elderly to carry out Activity of Daily Living (ADL). This study will be held on October 22, 2023 at the KH Ahmad Dahlan Mosque Jl. S.Parman, North Belitung, West Banjarmasin District, Banjarmasin City. The purpose of this study is to determine the level of independence of the elderly using the Barthel Index measurement tool through the Question and Answer method. According to the results of the discussion, it can be concluded that the level of independence of the elderly in the independent category is at a good health level in accordance with the results of the study conducted on the elderly congregation of the KH. Ahmad Dahlan Mosque. The results of this service are also expected by all participants to maintain the quality of the ADL that they have done.